Percepção etnobotânica dos apicultores do município de Marcelino Vieira, Rio Grande do Norte - Brasil - Câmara, Carlos Piffero (2019)
This study aimed to identify the ethnobotanical knowledge that beekeepers have about the honey flora in Marcelino Vieira, a southwestern municipality of the state of Rio Grande do Norte, which has a tradition in bee production, in contrast to the increasing prerogative of environmental degradation and decreased biodiversity, with the expansion of cities and agricultural areas over preserved areas. The actions of this study were performed from March to July / 2018. Through non-probabilistic sampling, 20 beekeepers were selected based on data from the Jefferson Fernandes de Medeiros Community Association. In order to obtain data, we used participant observation, free list, guided tour, field diary and application ofstructured form, according to Opinion CEP No. 2,698,897. Beekeepers cited 93 species with beekeeping potential for the region, of which 86% are native, of which 19 are Caatinga endemic, distributed in 37 botanical families, highlighting Fabaceae, which covers 21% of the species. According to the Use Value (VU ≥ 0.4), some species stood out, among them Combretum leprosum (1.85) and Croton sonderianus (1.8) were identified as the most important for local beekeeping. It is hoped that the information obtained may contribute to a better performance of the regional beekeeping, with the conservation of Caatinga plants and the valorization of the knowledge of the Potiguar beekeepers of Northeastern Brazil.